Current Trends in the Application of EEG in Neuromarketing: A Bibliometric Analysis - Ahmed Alsharif; Nor Zafir Md Salleh; Lina Pilelienė; Alhamzah F. Abbas; Javed Ali (Scientific Annals of Economics and Business)
Despite several neuroscience tools existing, electroencephalography (EEG) is the most used and favoured tool among researchers because of its relatively low cost and high temporal resolution. Our study aimed to identify the global academic research trends of the empirical EEG studies in neuromarketing. This paper adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to identify relevant articles. A bibliometric analysis software (VOSviewer) was used to evaluate thirty open-access articles found in the Scopus database between 2016 and 2020. We found that the USA is the most productive country with five research articles that used the EEG tool in marketing studies, followed by Australia, Italy, and Malaysia with three articles each. According to the most prolific journals in neuromarketing, it has been found that Frontiers in Neuroscience journal (CiteScore 5.4) is the most prolific journal with two articles and 25 total citations, followed by Scientific reports (CiteScore 7.1) with two articles and eighteen total citations, which lead us to infer that the publications’ number does not necessarily reflect the citations’ number. The study provides a profound and comprehensive overview of academic research that used EEG in marketing research.